A Model-Based Unloaded Test Method for Analysis of Braking Capacity of Elevator Brake. (21st November 2018) - Peng, Qifeng; Li, Zhongxing; Yuan, Hong; Huang, Guojian; Li, Shanqing; Sun, Xueli
Abstract : In order to improve the inspection efficiency and accuracy of the braking capacity of the elevator brake being used, a novel method for analyzing the full-loaded braking performance by using the unloaded braking performance is proposed, and a set of methods for measuring the braking torque is designed. Based on the analysis of the key factors that affect the mechanical performance of the elevator brake, the calculation model of the braking torque in the process of the emergency braking with the traction ratio of 2 : 1 is established, and the relationship between the braking torque and acceleration under different working conditions is analyzed. It is shown that, for the model assumed, the emergency braking torque is 1.56 times that of the static braking torque under 1.25 times the rated load. The braking torque increases linearly with the increase of braking acceleration. An elevator model being used is tested and calculated. The experimental results show that the braking acceleration measured by the experiment is 11.95% less than the theoretical value. And the analysis shows that, comparing with the traditional test method, the braking torque test method designed in this paper is more accurate and safe.